National level wealth inequality and socioeconomic inequality in adolescent mental wellbeing. (30th September 2020) - Dierckens, M; Weinberg, D; Huang, Y; Elgar, F; Moor, I; Augustine, L; Lyyra, N; De Clercq, B; Stevens, G W J M; Currie, C
Abstract: Background: Previous research established a positive association between national income inequality and socioeconomic inequalities in adolescent health, but little is known about the extent to which national level inequalities in accumulated financial resources (i.e. wealth) are associated with these health inequalities. Therefore, we examined the association between national wealth inequality and income inequality and socioeconomic inequalities in adolescent mental wellbeing. Methods: Data were from 17 countries participating in three successive waves (2010, 2014 and 2018) of the cross-sectional Health Behaviour in School-aged Children (HBSC) study. We combined individual-level data on adolescents' life satisfaction, psychological and somatic symptoms and socioeconomic status (SES) with country-level data on income and wealth inequality (n = 244771). We performed time-series analysis on a pooled sample of 48 country/year groups. Results: Higher levels of national wealth inequality were associated with fewer average psychological and somatic symptoms, while higher levels of national income inequality were associated with more psychological and somatic symptoms. No associations between either national wealth inequality or income inequality and life satisfaction were found. Smaller differences in somatic symptoms between higher and lower SES groups were found in countries with higher levels of national wealth inequality. In contrast, larger differences in psychological symptoms and life satisfaction (but not somatic symptoms) between higher and lower SES groups were found in countries with higher levels of national income inequality. Conclusions: Although both national wealth and income inequality are associated with (socioeconomic inequalities in) adolescent mental wellbeing, associations are in opposite directions. Further research is warranted to gain better understanding in the role of national wealth inequality on (socioeconomic inequalities in) adolescent health. Key messages: This is one of the first studies to examine if socioeconomic inequalities in adolescent mental wellbeing are associated with national wealth inequality independently from national income inequality. Opposing effects of national wealth inequality and income inequality on socioeconomic inequalities in adolescents' mental wellbeing warrant further research before policy recommendations can be made.